Impact of warming and deoxygenation on the habitat distribution of Pacific halibut in the Northeast Pacific. (23rd September 2022) - Franco, Ana C.; Kim, Hongsik; Frenzel, Hartmut; Deutsch, Curtis; Ianson, Debby; Sumaila, U. Rashid; Tortell, Philippe D.
Abstract: Ocean warming and deoxygenation are already modifying the habitats of many aerobic organisms. Benthic habitat in the Northeast Pacific is sensitive to deoxygenation, as low oxygen concentrations occur naturally in continental shelf bottom waters. Here, we examine the potential impacts of deoxygenation and ocean warming on the habitat distribution of Pacific halibut ( Hippoglossus stenolepis ), one of the most commercially important groundfish in North America. We combine fisheries‐independent Pacific halibut survey data (1998–2020) with oceanographic measurements and a regional ocean circulation model to investigate current and future (end of 21st century) influences of deoxygenation and warming on optimal Pacific halibut habitat. We use the observations and model output to derive a metabolic index of Pacific halibut‐specific suitable habitat. Our results show high Pacific halibut counts in regions where the metabolic index is greatest and demonstrate that interannual variability in Pacific halibut abundance is coherent with the Pacific Decadal Oscillation. Working with model projections, we examine potential future changes in suitable Pacific halibut habitat by the end of the century under a high carbon dioxide emissions scenario. These projections indicate that suitable Pacific halibut habitat may largely disappear off the coast of Washington state, retreating approximately 5° latitude northward. In bottom waters along coastal British Columbia and Alaska continental shelf, Pacific halibut habitat is projected to decrease by about 50%. Such habitat changes may potentially drive a northward shift in Pacific halibut, with significant implications for commercial fisheries.